(untitled) (Bangladesh Journal of Otorhinolaryngology, 2023)
Background: Patients with T1 T2 N0 mouth or tongue cancer that has been confirmed by a doctor may choose to have a neck dissection. Some say that nodal return of a T1 original tumor is well controlled, while others say that salvage is more often the exception than the rule. Objective: To determine the likelihood of recurrence in T1 or T2 early tongue carcinoma with or without neck dissection. Methods: The prospective cross-sectional clinical study was conducted from March 2021 to March 2023 at the Department of ENT and Head Neck Surgery, Combined Military Hospital, Dhaka. All 100 patients who presented with clinically determined T1 and T2 disease, as defined by the American Joint Committee on Cancer (AJCC), were treated at the Department of Otolaryngology of the Combined Military Hospital in Dhaka and underwent primary surgical resection of the tumor with or without neck dissection. The study eliminated cases of cancer involving the base of the tongue or recurring oral tongue cancer. Results: In the neck dissection group, 3(6%) experienced local recurrence, 2(4%) experienced regional recurrence, and 1 (2%) experienced both (local and regional recurrence). There will be no dissection. 10(20%) Local recurrence, 3 (6%), Regional recurrence, and 1 (2% combined local and regional recurrence). Recurrence was 4(8%) in the neck dissection group and 14(28%) in the no dissection group. Conclusion: In this study, the overall recurrence rate was 8% in neck dissection and 28% in no neck dissection. The overall recurrence rate in the no neck dissection group was significantly greater than in the neck dissection group. Bangladesh J Otorhinolaryngol 2023; 29(1): 5-10